Gender and COVID-19's Impacts on Global Agriculture, Food Security and Nutrition - Soule, Meredith (2020)
Meredith Soule POLICY SEMINAR Virtual Event - What do we need for a gender-sensitive Covid-19 response in agriculture and food security? Insights from research and practice MAY 21, 2020 - 09:30 AM TO 10:45 AM EDT